Institutionalization of Counter-Terrorism Cooperation in the Eurasian Area: Current Issues and Prospects - Ju. O. Karpenko; M. M. Shumilov (Евразийская интеграция: экономика, право, политика, 2021)
The objective is to define the main parameters and current state of the institutionalization of international anti-terrorist activities in the Eurasian area. At the same time, the authors focus is on the institutional and legal aspects of institutionalizing the fight against terrorism in formats of CIS, CSTO, SCO. Also, the article defines and characterizes the problematic field of the stable system formation for interaction between different anti-terrorist structures in the Eurasian space in the context of existing institutionalization models of anti-terrorist cooperation (UN, NATO, EU, etc.). Authors justified the assumptions about the institutionalization and possible prospects of the Eurasian anti-terrorist initiative and the role of Russia in its implementation.